2005
DOI: 10.1354/vp.42-2-230
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma with Metastasis to the Spleen in a Holstein Cow

Abstract: Abstract. Hepatocellular carcinoma (HCC) with metastasis to the spleen in a Holstein cow was studied by histopathologic and immunohistochemical methods. The tumor was characterized by a pseudoglandular (acinar) pattern with an associated fibrous stroma. Individual cells often had a ''hepatoid'' appearance but were interspersed with scattered cells exhibiting a clear, periodic acid-Schiff (PAS)-positive cytoplasm and small eccentric nuclei. This pattern was present in nodules found in both liver and spleen. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 9 publications
2
7
0
5
Order By: Relevance
“…All cattle affected in this study were adults, aged three years or older, similar to that reported by other authors (Anderson & Sandinson 1968, Wettimuny 1969, Braun et al 2005, Jeong et al 2005. Females were more affected than males, and, although few studies assessed a possible sex predilection for the development of liver tumors in cattle (Wettimuny 1969, Braun et al 2005, in dogs and cats it is known that there is no such predisposition (Patnaik et al 1981, Trigo et al 1982, Lawrence et al 1994, Liptak et al 2004, Flores et al 2013, Van Sprundel et al 2014.…”
Section: Discussionsupporting
confidence: 85%
“…All cattle affected in this study were adults, aged three years or older, similar to that reported by other authors (Anderson & Sandinson 1968, Wettimuny 1969, Braun et al 2005, Jeong et al 2005. Females were more affected than males, and, although few studies assessed a possible sex predilection for the development of liver tumors in cattle (Wettimuny 1969, Braun et al 2005, in dogs and cats it is known that there is no such predisposition (Patnaik et al 1981, Trigo et al 1982, Lawrence et al 1994, Liptak et al 2004, Flores et al 2013, Van Sprundel et al 2014.…”
Section: Discussionsupporting
confidence: 85%
“…Unfortunately, a large part of the diagnosis of HCC in cattle is perfomed out postmortem, consisting mostly of incidental findings in the slaughterhouses [5,7,12], with few reports on the clinical conditional of the animal. Consistent with the scarce reports available in the literature [6,16], the main complaint of the owner of this report was progressive weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…Although primary liver diseases are rare in farm animals, except for cases resultanting of intoxication [18], hepatocellular carcinoma (HCC) is the most frequent hepatic neoplasm in ruminants [15]. In cattle the reports are scarce [6,10,12], most of them coming from slaughterhouses, thus not allowing much data from HCC in this species [4,5,7,24].…”
Section: Introductionmentioning
confidence: 99%
“…A ocorrência de metástase nesta neoplasia é incomum, mas pode atingir 28% em gatos e 39% em bovinos, sendo mais frequentes em linfonodo, pulmão e peritônio no cão, e há relato de metástase no baço ,Cullen & Pop 2002, Jeong et al 2005. Contudo, no presente estudo observamos que haviam lesões nodulares no pâncreas e no rim na região córtico-medular, de distribuição multifocal, com características semelhantes às presentes no fígado, sugerindo que essas lesões eram metástases.…”
Section: Discussionunclassified